Efficacy of the flipped classroom method in virtual education in university students - Alva Miguel, Walter Hugo (2021)
Abstract The essential purpose of the study carried out was to objectively verify the effectiveness of the flipped classroom system in virtual educational processes in the specialty of Historical-Social Sciences of the Faculty of Education of the National University Federico Villarreal. To this end, an applied, descriptive comparative study was developed, with a longitudinal sectional experimental design and a quantitative approach. To fulfill this intention, a questionnaire was applied before and after the application of the system, to the experimental group and the control group, in order to verify if there were significant differences between these groups at the end of the experience. The instrument was validated through the opinion of experts and the reliability was verified with the Cronbach's Alpha test. This instrument was administered to a sample of 34 students, 17 of whom were from the experimental group and the other 17 from the control group. The "probability sampling" was used to select the sample component, because the conformation was carried out by lottery. The statistical design applied was the “comparison of means” using the SPSS version 22 program and the Student's “t” Ratio statistic, to compare the means and verify the hypotheses. It was found that the flipped classroom system significantly improves the performance of the Experimental Group with reference to the Control Group in learning the selected subjects. Keywords: Flipped classroom method, virtual education, efficiency.